NON PHENOLIC COMPOUNDS ISOLATED FROM THE LEAVES OF FERN Chingia sakayensis (Zeiller) Holtt - Suyatno Suyatno; Noor Cholies Zaini; Gunawan Indrayanto; Motoo Tori (Universitas Gadjah Mada, 2006)
Two non phenolic compounds namely a wax ester hexacosyl hexadecanoic and a steroid -sitosterol were isolated from the n-hexane extract of the fern Chingia sakayensis (Zeiller) Holtt's leaves. Their structures were elucidated on the basis of the spectrometric evidences (UV, IR, 1H-NMR, 13C-NMR, EIMS and HR-CIMS).